Effect of Irrigation System, Planting Density and Potassium Silicate Spraying on the Growth and Quality of Tomato - Athraa Hussein Hadi; Abdulraheem Assi Obaid (مجلة ديالى للعلوم الزراعية)
The experiment was carried out to study the irrigation systems, planting density and potassium silicate spraying on the growth and quality of tomato. The experiments included three factors, the type of drip irrigation systems (S) as: single line irrigation (S1) and Double line irrigation (S2). The planting densities (D): D1 (40 cm) (density: 12 plants); D2 (50 cm) (density: 10 plants) and D3 (60 cm) (density: 8 plants). The third factor was potassium silicate spraying (K): as: K0 (control); K1 (treated of plant with 1 mL L-1) and K2 (treated with 2 mL L-1). Using a factorial experiment within a split-plot design, main plots were allocated to irrigation systems (S1 and S2). The results showed that, the single irrigation system (S1) produced a significant superiority in acidity 0.560 %; vitamin C 34.958 mg; TSS 3.846 and lycopene 2.264 mg, compared with double line (S2) which showed superiority in β-carotene pigment 2.448 mg. Planting density at a distance of 60 cm produced the highest values in TSS 3.73; fruit hardness 3.590 kg cm2 -1 , β-carotene 2.41mg, while planting at 40 cm showed superiority in lycopene pigment 2.034 mg. Treatment with potassium silicate at a concentration of 1 mL L-1 (K1) was found to produce the highest lycopene and β-carotene, while a concentration of 2 mL L-1 had superiority in acidity and vitamin C. From the results, using the single irrigation system had superiority in producing tomato with high qualities, while planting tomato at a distance of 40 cm had superiority in most qualities characteristics